1986
DOI: 10.1097/00132582-198606000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epidural Analgesia on Plasma Catecholamines and Cortisol in Parturition

Abstract: To assess the effect of epidural block on plasma catecholamines and cortisol during labour and delivery, plasma epinephrine, norepinephrine and cortisol levels were determined in 26 healthy parturients, all of whom delivered vaginally (18 received a n epidural block, eight had meperidine 50 mg intramuscularly). We found a significant drop of plasma epinephrine and cortisol and no significant reduction of plasma norepinephrine 1 h after administration of epidural block compared to preblock values. Observing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 14 publications
(19 reference statements)
0
19
1
2
Order By: Relevance
“…11,12,14 Blood pressure responses during labour may depend on pain and stress, but possibly also on neurohumoral control independent of pain. 11,133,134 The increases in HR during stage 1 contractions in Study II were greater than previously reported increases in HR. 10,11,17,18 One former research group found decreases in HR during contractions, which they ascribed to the baroreceptor reflex.…”
Section: Haemodynamics During Contractionscontrasting
confidence: 63%
See 1 more Smart Citation
“…11,12,14 Blood pressure responses during labour may depend on pain and stress, but possibly also on neurohumoral control independent of pain. 11,133,134 The increases in HR during stage 1 contractions in Study II were greater than previously reported increases in HR. 10,11,17,18 One former research group found decreases in HR during contractions, which they ascribed to the baroreceptor reflex.…”
Section: Haemodynamics During Contractionscontrasting
confidence: 63%
“…While stage 1 contractions caused either increases or decreases in SVR, stage 2 contractions led to considerable increases in SVR in all parturients. In view of blood pressure increases 11,12,14,15 and adrenergic activation 133,134 during labour, the decreases in SVR during contractions in some of our parturients, in the absence of epidural analgesia, were rather unexpected. Most previous studies did not explicitly report on SVR, but one author group also found decreases in SVR during stage 1 contractions.…”
Section: 14mentioning
confidence: 74%
“…An association between uterine contractility and the administration of meperidine has been reported [21], and several explanations have been proposed for this effect [22][23][24]. Pain relief may increase uterine contractility by causing a decrease in adrenaline concentration [23,24]. Moreover, administering meperidine during labor was found to be associated with changes in cervical proteases [25].…”
Section: Introductionmentioning
confidence: 99%
“…Many different explanations supporting the effect of meperidine on the duration of labor have been published, such as changes in cervical protease levels 5 and pain relief with a subsequent decrease in catecholamine levels. 6,7 To our knowledge, there have been only two placebocontrolled trials that evaluated the use of meperidine to shorten the duration of labor, but these studies produced conflicting results. Sosa et al 8 found no statistically significant difference between meperidine (100 mg in 50 mL saline, slow intravenous administration over 15 min) and placebo groups with respect to the duration of labor in women diagnosed with uterine dystocia during the first stage of labor.…”
Section: Introductionmentioning
confidence: 99%